Archaeomagnetism in the Levant and Mesopotamia Reveals the Largest Changes in the Geomagnetic Field - Shaar, Ron; Gallet, Yves; Vaknin, Yoav; Gonen, Lilach; Martin, Mario A. S.; Adams, Matthew J.; Finkelstein, Israel (Journal of geophysical research. Solid earth, 2022)
Our understanding of geomagnetic field intensity prior to the era of direct instrumental measurements relies on paleointensity analysis of rocks and archaeological materials that serve as magnetic recorders. Only in rare cases are absolute paleointensity data sets continuous over millennial timescales, in sub‐centennial resolution, and directly dated using radiocarbon. As a result, fundamental properties of the geomagnetic field, such as its maximum intensity and rate of change have remained a subject of lively discussion. Here, we place firm constraints on these two quantities using Bayesian modeling of well‐dated archaeomagnetic intensity data from the Levant and Upper Mesopotamia. We report new data from 23 groups of pottery collected from 18 consecutive radiocarbon‐dated archaeological strata from Tel Megiddo, Israel. In the Near East, the period of 1700–550 BCE is represented by 84 groups of archaeological artifacts, 55 of which were dated using radiocarbon or a direct link to clear historically dated events, providing unprecedented sub‐century resolution. Moreover, stratigraphic relationships between samples collected from multi‐layered sites enable further refinement of the data ages. The Bayesian curve shows four geomagnetic spikes between 1050 and 600 BCE, with virtual axial dipole moment (VADM) reaching values of 155–162 ZAm2, much higher than any prediction from geomagnetic field models. Rates of change associated with the four spikes are ∼0.35–0.55 μT/year (∼0.7–1.1 ZAm2/year), at least twice the maximum rate inferred from direct observations spanning the past 180 years. The increase from 1750 to 1030 BCE (73–161 ZAm2) depicts the Holocene's largest change in field intensity. Plain Language Summary The strength of Earth's magnetic field changes in an unpredictable manner. Understanding these changes requires precise information on how the field has changed in the past. Direct instrumental measurements of magnetic field intensity began in the 1840s, providing only a short time window into past intensity changes. Here, we explore the ancient field by analyzing a rare collection of radiocarbon‐dated archaeological materials from stratified archaeological settlements and historically dated burnt structures in the Levant and Mesopotamia. We use new data from Tel Megiddo (Armageddon) to construct a continuous curve of geomagnetic field intensity spanning 2,500 years, with unprecedented detail and resolution. The curve depicts the evolution of a high‐intensity anomaly, the largest change in intensity observed during the Holocene. Between 1750 and 1050 BCE, the field rapidly increased to values greater than twice those of today, much higher than any prediction derived from available geomagnetic field models. Subsequent oscillations between 1050 and 550 BCE, with extreme peaks, namely “geomagnetic spikes,” reveal change rates of at least twice as fast as the fastest change observed since the advent of direct measurements. Levantine archaeomagnetic data represent a case study in which archaeology provides crucial constraints on the geomagnetic field behavior. Key Points Archaeomagnetic intensity data from 23 groups of pottery collected from 18 consecutive radiocarbon‐dated strata in Tel Megiddo (Israel) The Levantine Archaeomagnetic Curve (LAC): a Bayesian radiocarbon‐calibrated archaeointensity curve of the Levant and Mesopotamia Four geomagnetic spikes between 1050 and 600 BCE define new constraints for maximum field intensity and secular variation rates